Yogasanas as a Neurodynamic Mobilisation Tool in the Treatment of Sciatica: Yogasanas as a Neurodynamic Mobilisation Tool in the Treatment of Sciatica - Baxi, Gaurang D.; Mokashi, Madhav G.; Borade, Nirmala G.; Palekar, Tushar J.; Panse, Rasika (National Journal of Integrated Research in Medicine, 2018)
Background & objectives: Neurodynamic mobilisation tests are well established techniques for mobilising nerves. Yogasanas are also independently recognised for their benefits in various conditions and ailments. This study compares Paschimotanasana, which is similar in position to the Neurodynamic mobilisation tests for the sciatic nerve. Methods: 32 patients suffering from sciatica were enrolled in either of the two treatment groups- Neurodynamic mobilisation and Yogasanas. The Yogasana group has to perform 7 asanas, out of which only one Yogasana (Paschimotanasana) would be similar to slump test. Pain was assessed using the Visual analogue pain scale (VAS). Results: There was no statistically significant difference (P>0.05) between the VAS scores obtained between the two groups. However, the Yogasana group took more number of days (2 weeks) for pain relief compared to the Neurodynamic mobilisation group. Interpretation & conclusion: Yogasanas can be used for mobilizing peripheral nerves, and with regular use reduce their mechanosensitivity. While the patient can self mobilize the nerve, the role of physiotherapist will be in planning appropriate Yogasanas and teach the programme as a package initially, to instruct about overstretching and protect blood vessels travelling with nerves and supervise intermittently.[Gaurang B NJIRM 2017; 8(4):48-52]